New records of Petunia (Solanaceae) for theArgentinean flora - Ando, Toshio; Soto, Maria Silvina; Suarez, Enrique Ysidro (Instituto de Botánica Darwinion, 2019)
Petunia interior and P. guarapuavensis are reported for the first time for the Argentinean flora, andtheir geographical distributions are updated.